Analysis on Energy Saving of 350 MW Supercritical Turbine with Low-Grade Energy Heating Technology - Guoqiang ZHOU; Xianming SUN (Zhongguo dianli)
The extraction of steam for heat supply in traditional combined heat and power generation plant is found with several issues such as low heating capacity, large power loss, high comprehensive energy consumption and low exergy efficiency. In this paper, the low-grade energy heating technology on the basis of heat classifications for wet cooling units is utilized in the energy saving retrofit project of a 350 MW supercritical cogeneration unit. The operation results indicate that after the retrofit, the heating capacity and the power generation output of the unit increased by 35% and over 8% respectively under the same main steam mass flow. In addition, as the annual heating capacity is expanded by 1.886 5 million GJ, the power generation output has increased by 83.9 million kW·h with year-over-year revenue growth about 93.416 million RMB during the heat supply period. That means after the completion of the retrofit project 126.9 thousand tons of coal equivalent have been saved for the social society and the CO2 emission has been reduced by 330 thousand tons.